Illuminae / 1. - Kaufman, Amie (Illuminae files, 2015)
"The planet Kerenza is attacked, and Kady and Ezra find themselves on a space fleet fleeing the enemy, while their ship's artificial intelligence system and a deadly plague may be the end of them all"--Provided by publisher.